Pengaruh Kualitas Produk Dan Brand Trust Terhadap Keputusan Pembelian Air Minum Dalam Kemasan Merek Club - Permatasari, Dhiah; Pudjoprastyono, Hery (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Drinking water is a basic need that must be fulfilled because more than half of the composition of the human body is water. However, the quality of water currently is not suitable for consumption because it contains many harmful bacteria. Another alternative to meet the need for drinking water is bottled drinking water. Seeing the large number of needs for AMDK, it should be in line with the increasing sales of various AMDK producing companies. However, the Club has experienced decreased sales fluctuations compared to other competitor companies. So, this study aims to determine the effect of product quality and brand trust on the decision to purchase Club Brand Bottled Drinking Water. The research was conducted online and data collection was carried out by distributing questionnaires via the g-form. The technique used to take samples was purposive sampling with a population of 98 respondents. The analysis technique used is component-based Structural Equation Modeling (SEM) method using tools Patrial Least Square (PLS). The results of the hypothesis testing of this study show that the product quality variable and Brand Trust variable have a significant and positive direction influence on the decision to purchase Club Brand Bottled Drinking Water.